Development of an Aryloxazole Derivative as a Brain-Permeable Anti-Glioblastoma Agent - Shin, Seulgi; Lim, Sungsu; Song, Ji Yeon; Kim, Dohee; Choi, Min Jeong; Gadhe, Changdev G.; Park, A. Young; Pae, Ae Nim; Kim, Yun Kyung (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Glioblastoma drug development has been difficult due to the extremely low blood brain barrier (BBB) penetration of conventional anti-cancer agents. P-glycoprotein, an efflux membrane transporter, is responsible for the poor brain uptake of small and hydrophobic drug substances. To develop brain-penetrable anti-tumor agents, we designed colchicine derivatives containing an aryloxazole moiety, which is known to inhibit P-glycoprotein. Among those tested, an aryloxazole derivative named KIST-G1 showed the strongest anti-glioblastoma cell proliferation activity (IC50 = 3.2 ± 0.8 nM). Compared to colchicine, KIST-G1 showed dramatically increased BBB-permeable properties presenting 51.7 ± 0.5 (10−6 cm/s) parallel artificial membrane permeability assay (PAMPA) permeability and 45.0 ± 6.0% of P-gp inhibition. Aid by the BBB-permeable properties, KIST-G1 (5 mg/kg) suppressed glioblastoma cell growth and migration almost completely in the brain of glioblastoma xenograft models by showing 98.2 ± 0.1% reduced tumor area compared with phosphate buffered saline (PBS)-injected control. In comparison, temozolomide, which is the most widely used drug for glioblastoma, showed only moderate effects. Our results demonstrate the effectiveness of an aryloxazole moiety in targeting brain tumors and suggest KIST-G1 as a potent anti-glioblastoma agent.